Suggestion for Brown Event Remarks
This document provides suggested remarks for a campaign event featuring Governor Brown, focusing on criticizing Jane Tolmach's Republican opponent, Chuck Imbrecht. The speech argues that Imbrecht's image as a moderate reformer is contradicted by campaign finance records showing substantial backing from corporate interests, political action committees, and Republican organizations. It lists specific contributors to portray him as indebted to narrow special interests and questions his credibility, including allegations that he distributed a misleading questionnaire implying he was the incumbent Assemblyman. The remarks frame the election as a matter of honesty and integrity, contrasting Tolmach's grassroots support with her opponent's financial backing and calling on supporters to intensify get-out-the-vote efforts.